1992
DOI: 10.1080/09553009214551851
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, Uptake and Dissolution of241AmO2Particles in Dog Alveolar Macrophagesin Vitro

Abstract: Because alveolar macrophages play a role in the pulmonary clearance of inhaled particles, experiments were conducted to investigate the toxicity of 241AmO2 particles to alveolar macrophages and the role of these macrophages in the dissolution of 241AmO2 particles. Beagle dog pulmonary alveolar macrophages obtained by bronchopulmonary lavage were exposed in vitro to selected concentrations of 241AmO2. Macrophage viability determined by trypan-blue dye exclusion technique and the ability of the alveolar macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…range of 5 (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), it is plausible to conclude that the intracellular mechanism of particle dissolution is controlled by these two parameters. However, at this moment we cannot exclude other mechanisms of IPD resulting from proteolytic enzymes, oxygen radicals, chelators, precipitators, etc., that are contained in the phagolysosomal plasma (20).…”
Section: Mechanisms Of Intracellular Particle Dissolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…range of 5 (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), it is plausible to conclude that the intracellular mechanism of particle dissolution is controlled by these two parameters. However, at this moment we cannot exclude other mechanisms of IPD resulting from proteolytic enzymes, oxygen radicals, chelators, precipitators, etc., that are contained in the phagolysosomal plasma (20).…”
Section: Mechanisms Of Intracellular Particle Dissolutionmentioning
confidence: 99%
“…In another study, dissolution of polydisperse, radioactive 244AmO2 particles was determined in cultured AM obtained from monkeys, dogs, and rats (46,47). Dissolution in the cell culture system increased linearly to 10% of the initial particle amount after 3 days of incubation, whereas dissolution ofthe AmO2 particles in the culture medium only was constant at 1% ofthe initial particle amount.…”
Section: Intracellular Particle Dissolutionmentioning
confidence: 99%
“…43 Similar to 198g Au NPs, 141 CeO 2 NPs showed an approximately linear increase in uptake (at picograms per cell level) in mouse fibroblast cell line Balb/ 3T3 as a function of 141 CeO 2 NP concentration. 44 A rapid increase in the cell-associated fraction of 241 AmO 2 particles (internalized in or adsorbed on cells) was observed for dog pulmonary alveolar macrophages during the first 2 h of exposure, and nearly 75% of the initial amount of 241 AmO 2 was cellassociated after 5 h. 45 After 72 h in cultures, 10% of the cellassociated 241 AmO 2 was dissolved by alveolar macrophages, which might play a role in the short-term pulmonary clearance of inhaled 341 AmO 2 particles. An interspecies comparison of the phagocytosis and dissolution of 241 AmO 2 particles by rat, dog, and monkey alveolar macrophages showed that dog and monkey macrophages took up 241 AmO 2 particles at similar rates, whereas rat macrophages phagocytosed only 60% of the amount phagocytosed by dog and monkey macrophages.…”
Section: Applications Of Radioactive-isotope-labeled Metal-containing...mentioning
confidence: 99%
“…Similar to 198g Au NPs, 141 CeO 2 NPs showed an approximately linear increase in uptake (at picograms per cell level) in mouse fibroblast cell line Balb/3T3 as a function of 141 CeO 2 NP concentration . A rapid increase in the cell-associated fraction of 241 AmO 2 particles (internalized in or adsorbed on cells) was observed for dog pulmonary alveolar macrophages during the first 2 h of exposure, and nearly 75% of the initial amount of 241 AmO 2 was cell-associated after 5 h . After 72 h in cultures, 10% of the cell-associated 241 AmO 2 was dissolved by alveolar macrophages, which might play a role in the short-term pulmonary clearance of inhaled 341 AmO 2 particles.…”
Section: Radioactive Isotopes As Tracers For Metal-containing Enginee...mentioning
confidence: 99%
“…La capacité de phagocytose ainsi que la viabilité des macrophages sont aussi altérées in vitro après addition de 241Am0, dans le milieu de culture (Taya et Mewhinney, 1992). Cependant pour toutes ces études, la dose réelle délivrée aux cellules demeure inconnue.…”
Section: Introductionunclassified